(untitled) (Bangladesh Journal of Zoology, 2015)
Production feasibility of monosex nile tilapia, Oreochromis niloticus was studied in eight brackish water ponds, where tilapia fries with the average body weight (ABW) of 0.15 g were stocked at a density of 5/m2. Salinity of the ponds varied from 11 ppt to 14 ppt. Fishes was fed with floating feed containing 35% crude protein. After 105 days of culture, production of tilapia was 6334.20- 8099.50 kg/ha with an average mean of 7456.35 ± 589.60 kg/ha. This production was achieved when average body weight and survival of tilapia was 176.50 ± 18.44 g and 84.42 ± 7.23%, respectively. This growth and production tilapia was higher and very much comparable to the production of tilapia reported from freshwater bodies. The study indicates that tilapia can be grown as crop diversification in brackishwater ponds, where stocking of shrimp now become risky due to invasion of diseases Bangladesh J. Zool. 42(2): 261-269, 2014